Pengembangan Media Pembelajaran Google Spreadsheet di Dayah Darul Ihsan Aceh Besar - Ahmad Damanhuri Adnan; Azhar Azhar (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2022)
The Paperlees concept is to reduce the use of paper in schools with the aim of effectiveness and efficiency in school management. All of this can be done with the help of Information and Communication Technology (ICT) which has developed rapidly at this time. The World 4.0 era with increasingly advanced technology turned out to have a positive impact on various lines of life. Even in educational institutions, even though technological advances have also begun to be applied. For example, using Google Sheets for attendance, collecting test scores, and student data and others. However, the use of this technology will fail if there is no special training for teachers or educators. Using Google Sheets for attendance and assessors makes it very easy for teachers and academic departments to collect data in real-time. Based on this fact, writing this article aims to explain what steps were taken by Dayah Darul Ihsan in training educators about Google Spreadsheets. This article combines qualitative data from 3 teaching staff respondents to get objective results about the ease and difficulty of using Google Sheets. Based on field studies, it was found that it was easy and several obstacles in using Google Spreadsheet by teachers. convenience; data connection in real-time between the teacher who teaches the homeroom and the academic division of Dayah. Constraint; the small screens of Android devices, the large number of old teaching staff who have difficulty using the media and the limited access to the WIFI network at Dayah Darul Ihsan. This study is considered new because it describes training on the use of technology at Dayah educational institutions. The findings from this article can be used in developing and optimizing the use of technology in Dayah/Madrasah. Maximum use of technology can improve the quality of education in Aceh and Indonesia in general.